The Design to Limit Regulations Governing Regional Head Elections - Siboy, Ahmad; Rafiqi, Ilham Dwi (Faculty of Law, University of Muhammadiyah Malang, 2026)
This research seeks to elaborate on the urgency and the design offered to limit regulations governing regional head elections (Pilkada). The main problem identified is the distribution of regional election norms across various types of regulations, which causes anomalies, conflicting norms, and dualism of interpretation by judicial institutions, such as differences in decisions between the Supreme Court and the Constitutional Court. Using normative-juridical research methods and statutory, conceptual, historical, and case-based approaches, this research reveals that the limitation in question serves as the initial milestone in constructing fair, effective, and efficient legal frameworks to regulate Pilkada with legal certainty. Philosophically, limiting the proliferation of norms is necessary to maintain the integrity of the local democratic system through the dimensions of ontology, epistemology, and axiology. The results of the study indicate that the most ideal design for limiting regional election regulations consists of three levels: the 1945 Constitution of the Republic of Indonesia as the constitutional basis, the Law as the primary regulation, and the Regulation of the Election Organising Institution (especially the General Elections Commission) as the technical delegation regulation. This model is considered the most appropriate, as it covers everything from abstract norms to concrete technicalities, guarantees legal certainty, and minimizes the influence of elite political interests in shaping regulations. The implementation of this design is expected to realise a more democratic, accountable, and equitable regional election governance.